NON-CONTRAST ENHANCED MULTI-SLICE CT-KUB IN RENAL COLIC: SPECTRUM OF ABNORMALITIES DETECTED ON CT KUB AND ASSESSMENT OF REFERRAL PATTERNS - Ali, Azmat; Akram, Faiza; Hussain, Shaukat; Janan, Zubair; Gillani, Syed Yasir Hussain (Journal of Ayub Medical College Abbottabad, 2019)
Background: Renal colic is a common problem and significant number of patients presenting to ER, ED are suffering from acute or chronic renal colic. The conventional methods of investigating patients with renal colic are urine routine examination, plain radiograph for KUB (kidneys, ureters and bladder) and ultrasound followed by intravenous urography. Now a days non contrast enhanced computed tomography of kidneys, ureters and bladder is the first line investigation in suspected upper urinary tract obstruction. Radiation dose is one of the major limitations of CT KUB. Other limitations are cost and availability. The sensitivity and specificity of CT KUB is extremely high in the diagnosis of stones. Methods: This cross-sectional descriptive study was conducted in the department of Radiology Ayub Medical Teaching Institution Abbottabad from 1st July 2017 to 30th May 2018. Information obtained from history, clinical examination and CT KUB, ultrasound were recorded in an approved and prescribed pro forma. Results: Among total 350 patients, majority were male 66% and the age of study population ranged from 20 to 60 years. Most of the patients presented with flank pain and microscopic hematuria. Calculi were detected in 52 %. Patients with non obstructing stones were 63 %, ureteric stones and hydronephrosis were 22 %, ureterovesicle junction stone 4%. Patients with stones and incidental findings made 12.8% of the study population having abnormal CT KUB. Conclusion: Non contrast enhanced CT KUB, performed in a suitable clinical scenario, is an excellent imaging investigation for patients having renal colic and the initial ultrasound is inconclusive. In majority of cases it identifies the cause of lumbar or pelvic pain. This modality has the added advantage of showing alternate causes for pain other than stones. Keywords: Renal colic; CT KUB; abnormalities;